1998
DOI: 10.1159/000025592
|View full text |Cite
|
Sign up to set email alerts
|

Wall Remodeling after Wall Shear Rate Normalization in Rat Mesenteric Arterial Collaterals

Abstract: Previous studies have demonstrated endothelial and smooth muscle hyperplasia occur during arterial luminal expansion associated with elevation of arterial wall shear rates. The current study investigated whether remodeling induced by elevated wall shear would ultimately result in a vessel with intimal and medial cell densities and other wall characteristics similar to control arteries. A rat mesenteric model was used in which collateral wall shear is restored to normal 4 weeks after arterial occlusion. Twelve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…After contrast enhancement, the luminal area, luminal area ϩ intimal area, and luminal ϩ intimal ϩ medial areas were determined by image analysis with gray level thresholding to select only the region to be measured. Previous measurements performed in this manner (6) have confirmed that this method provided results similar to manual tracing. The medial area (M) was calculated as follows:…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…After contrast enhancement, the luminal area, luminal area ϩ intimal area, and luminal ϩ intimal ϩ medial areas were determined by image analysis with gray level thresholding to select only the region to be measured. Previous measurements performed in this manner (6) have confirmed that this method provided results similar to manual tracing. The medial area (M) was calculated as follows:…”
Section: Methodssupporting
confidence: 72%
“…Wall shear level is increased at this location (Table 1), and the rate and magnitude of expansion is correlated with the shear stimulus (38). The observations that arterial luminal expansion in this model occurs where wall shear is elevated, is correlated with the degree of shear elevation, and ceases after wall shear rate is normalized (6,38,40,41) suggest that wall shear is important at least as a molding influence if not as the primary stimulus. For these reasons, we consider the luminal expansion observed in these collaterals to be flow or shear mediated.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The peak at day 8 preceded the increase in CSA, consistent with the expression of PCNA preceding hypertrophy compared with CSA also observed by Tulis et al, 22 although this appeared at an earlier time point (days 3 through 7). The late peak of PCNA seen at day 32 could be related to a later phase of remodeling appearing beyond 4 weeks, as observed by Fath et al 32 A regulation of the balance between cell proliferation and cell death may be the most important mechanism for remodeling, as has been suggested for embryonic development and normal tissue homeostasis (for review, see Best et al 33 and Hamet et al). 34 This is supported by the present study, where apoptosis determined by DNA laddering was more frequent in both the LF and HF arteries compared with control ( Figure 4B).…”
Section: Discussionmentioning
confidence: 71%
“…Two weeks of altered blood flow induced milder changes in external diameters and medial area compared with the previous study. Nonetheless, inasmuch as Unthank and colleagues 7,26 have shown that flow alterations lead to an initial abrupt change in vascular structure (within 1 week) followed by a slower adaptation over the subsequent months, the 2-week alteration is sufficiently long for examining mechanisms responsible for earlier structural remodeling in this model. Ligated arteries displayed significantly reduced circumferential distensibility compared with control arteries, despite the reduction in medial mass.…”
Section: Mechanical and Structural Alterations 2 Weeks After Arterialmentioning
confidence: 93%